Efektifitas Pemberian Terapi Akupunktur Antara Titik Baihui (GV 20) Dengan Titik Anmian (EX-HN 16) Pada Lansia Dengan Kasus Insomnia Di Panti Wreda Darma Bakti Surakarta - Sri Yatmihatun; Heni Nur Kusumawati; Joko Tri Haryanto (Jurnal Keterapian Fisik, 2016)
Abstract: Insomnia, Elderly, Acupuncture Therapy. The purpose of this study was to determine the effectiveness of acupuncture therapy between points Baihui (GV 20) with a point Anmian (EX-HN 16) in the elderly with insomnia cases in Hospice Surakarta. This research method using cross-sectional approach experimental method, using analysis Chi-Square Test. The results of analysis X2 = 4.821; p 0,028 in group therapy point Baihui (GV 20) and in group therapy Anmian point (EX-HN 16). Anmian point acupuncture therapy (EX-HN 16) is more effective than acupuncture point Baihui (GV 20) for acupuncture point Amnian (EX-HN 16) over banyan eliminate complaints decreased quality of sleep (66.7%).Keywords: Insomnia, Elderly, Acupuncture Therapy.